ANTAGONISTIC EFFECT OF FOUR FUNGAL ISOLATES TO GANODERMA BONINENSE, THE CAUSAL AGENT OF BASAL STEM ROT OF OIL PALM - OKKY SETYAWATI DHARMAPUTRA (BIOTROPIA, 1989)
ANTAGONISTIC EFFECT OF FOUR FUNGAL ISOLATES TOGANODERMA BONINENSE, THE CAUSAL AGENT OF BASAL STEM ROT OF OIL PALM